Functionalized 6-(piperidin-1-yl)-8, 9-diphenyl purines as inverse agonists of the CB1 receptor – SAR efforts towards selectivity and peripheralization. Issue 16 (15th August 2019) - Amato, George; Wiethe, Robert; Manke, Amruta; Vasukuttan, Vineetha; Snyder, Rodney; Runyon, Scott; Maitra, Rangan
Graphical abstract: Abstract: Antagonists of type 1 cannabinoid receptors (CB1) may be useful in treating diabetes, hepatic disorders, and fibrosis. Otenabant (1 ) is a potent and selective CB1 inverse agonist that was under investigation as an anti-obesity agent, but its development was halted once adverse effects associated with another marketed inverse agonist rimonabant (2 ) became known. Non-tissue selective antagonists of CB1 that have high levels of brain penetration produce adverse effects in a small subset of patients including anxiety, depression and suicidal ideation. Currently, efforts are underway to produce compounds that have limited brain penetration. In this report, novel analogs of1 are explored to develop and test strategies for peripheralization. The piperidine of1 is studied as a linker, which is functionalized with alkyl, heteroalkyl, aryl and heteroaryl groups using a connector in the form of an amine, amide, sulfonamide, sulfamide, carbamate, oxime, amidine, or guanidine. We also report more polar replacements for the 4-chlorophenyl group in the 9-position of the purine core, which improve calculated physical properties of the molecules. These studies resulted in compounds such as75 that are potent inverse agonists of hCB1 with exceptional selectivity for hCB1 over hCB2. SAR studies revealed ways to adjust physical properties to limit brain exposure.